2006
DOI: 10.1007/s10722-005-2641-6
|View full text |Cite
|
Sign up to set email alerts
|

A Preliminary Comparative Evaluation of Genetic Diversity between Chinese and Japanese Wild Soybean (Glycine soja) Germplasm Pools using SSR markers

Abstract: The wild soybean, an annual self-pollinating plant, is the progenitor of soybeans and is extensively distributed in the Far East of Russia, the Korea peninsula, China and Japan. Geographically, Japan is surrounded by sea and insulated from China. We preliminarily evaluate whether the Japanese and Chinese wild soybean germplasm pools are genetically differentiated from each other using SSR markers. The results showed that the two pools have great genetic differentiation. Some loci presented obvious differences … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
18
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 23 publications
5
18
1
Order By: Relevance
“…Among different types of DNA markers being utilized for molecular characterization and genetic diversity analysis in plants, simple sequence repeats (SSR) markers are considered as molecular marker of choice due to their abundance, high polymorphism rate and high reproducibility. SSR markers have been widely used in the genetic diversity studies of the soybean germplasm collections worldwide and high levels of polymorphism at SSR loci have been reported for both the number of alleles per locus and the gene diversity (Maughan et al 1995;Abe et al 2003;Wang et al 2006Wang et al , 2010Fu et al 2007;Wang and Takahata 2007;Li et al 2008;Singh et al 2010;Tantasawat et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Among different types of DNA markers being utilized for molecular characterization and genetic diversity analysis in plants, simple sequence repeats (SSR) markers are considered as molecular marker of choice due to their abundance, high polymorphism rate and high reproducibility. SSR markers have been widely used in the genetic diversity studies of the soybean germplasm collections worldwide and high levels of polymorphism at SSR loci have been reported for both the number of alleles per locus and the gene diversity (Maughan et al 1995;Abe et al 2003;Wang et al 2006Wang et al , 2010Fu et al 2007;Wang and Takahata 2007;Li et al 2008;Singh et al 2010;Tantasawat et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Japanese wild soybean is likely to be a descendant of the species at that time, which migrated with the motion of the Pacific plate. A study showed the genetic differentiation between Chinese and Japanese wild soybeans (Wang and Takahata 2007). Our present study showed that Tibetan wild soybean, with lower genetic diversity (Tables 3 and 5), differed genetically from other regional wild soybean populations (Table 6 and Fig.…”
Section: Discussionmentioning
confidence: 44%
“…SSRs molecular markers have been widely applied in the genetic diversity studies of the soybean germplasm (Abe et al, 2003;Wang et al, 2006;Fu et al, 2007;Li et al, 2008;Wang & Takahata, 2007;Wang et al, 2008;Yoon et al, 2009). The advantages of SSR over other types of molecular markers are that they are abundant, have a high level of polymorphism, are codominant, can be easily detected with PCR and typically have a known position in the genome.…”
Section: Ssrs (Simple Sequence Repeats)mentioning
confidence: 99%